THE DEVELOPMENT OF THE CREATIVITY OF STUDENTS WITH THE HELP OF GAME METHODS OF TEACHING (Scientific journal of the Fergana State University, 2024)
This article discusses various gaming techniques aimed at developing students' creativity. Particular attention is paid to role-playing games and construction as examples of methods that promote the formation of creative skills and abilities. The advantages of game teaching methods and methods of their successful integration into the educational process are also considered. The purpose of this review is to demonstrate how game-based teaching methods can be a powerful tool for developing student creativity, promoting not only the deepening of knowledge, but also the development of creative thinking, self-expression and innovative approaches to problem solving.